Guanine-modified inhibitory oligonucleotides efficiently impair TLR7- and TLR9-mediated immune responses of human immune cells. - Franziska Römmler; Monika Hammel; Anna Waldhuber; Tina Müller; Marion Jurk; Eugen Uhlmann; Hermann Wagner; Jörg Vollmer; Thomas Miethke (PLoS ONE)
Activation of TLR7 and TLR9 by endogenous RNA- or DNA-containing ligands, respectively, is thought to contribute to the complicated pathophysiology of systemic lupus erythematosus (SLE). These ligands induce the release of type-I interferons by plasmacytoid dendritic cells and autoreactive antibodies by B-cells, both responses being key events in perpetuating SLE. We recently described the development of inhibitory oligonucleotides (INH-ODN), which are characterized by a phosphorothioate backbone, a CC(T)XXX3-5GGG motif and a chemical modification of the G-quartet to avoid the formation of higher order structures via intermolecular G-tetrads. These INH-ODNs were equally or significantly more efficient to impair TLR7- and TLR9-stimulated murine B-cells, macrophages, conventional and plasmacytoid dendritic cells than the parent INH-ODN 2088, which lacks G-modification. Here, we evaluate the inhibitory/therapeutic potential of our set of G-modified INH-ODN on human immune cells. We report the novel finding that G-modified INH-ODNs efficiently inhibited the release of IFN-α by PBMC stimulated either with the TLR7-ligand oligoribonucleotide (ORN) 22075 or the TLR9-ligand CpG-ODN 2216. G-modification of INH-ODNs significantly improved inhibition of IL-6 release by PBMCs and purified human B-cells stimulated with the TLR7-ligand imiquimod or the TLR9-ligand CpG-ODN 2006. Furthermore, inhibition of B-cell activation analyzed by expression of activation markers and intracellular ATP content was significantly improved by G-modification. As observed with murine B-cells, high concentrations of INH-ODN 2088 but not of G-modified INH-ODNs stimulated IL-6 secretion by PBMCs in the absence of TLR-ligands thus limiting its blocking efficacy. In summary, G-modification of INH-ODNs improved their ability to impair TLR7- and TLR9-mediated signaling in those human immune cells which are considered as crucial in the pathophysiology of SLE.